2021
DOI: 10.3390/ma14020447
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation into the Effect of Pyrolysis on Chemical Forms of Heavy Metals in Sewage Sludge Biochar (SSB), with Brief Ecological Risk Assessment

Abstract: Experimental investigations were carried out to study the effect of pyrolysis temperature on the characteristics, structure and total heavy metal contents of sewage sludge biochar (SSB). The changes in chemical forms of the heavy metals (Zn, Cu, Cr, Ni, Pb and Cd) caused by pyrolysis were analyzed, and the potential ecological risk of heavy metals in biochar (SSB) was evaluated. The conversion of sewage sludge into biochar by pyrolysis reduced the H/C and O/C ratios considerably, resulting in stronger carboniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…The organic-bound state and the residual state are not easily absorbed by organisms in the environment and belong to the stable state. The exchangeable state, carbonate-bound state, and Fe-Mn oxide binding state are easily absorbed directly or indirectly and belong to the unstable state [20]. Many scholars have conducted research on heavy metal pollution using the Tessier sequential extraction method in samples of soils [21], sediments [22], and sewage sludge [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…The organic-bound state and the residual state are not easily absorbed by organisms in the environment and belong to the stable state. The exchangeable state, carbonate-bound state, and Fe-Mn oxide binding state are easily absorbed directly or indirectly and belong to the unstable state [20]. Many scholars have conducted research on heavy metal pollution using the Tessier sequential extraction method in samples of soils [21], sediments [22], and sewage sludge [15,23].…”
Section: Introductionmentioning
confidence: 99%
“…The potential risk of heavy metals in sewage sludge can be reduced by pyrolysis with variation of temperature [55]. The increase in temperature from 300 to 700 • C, increase the concentration of zinc (Zn), chromium (Cr), nickel (Ni), and copper (Cu), whereas the concentration of lead (Pb) and cadmium (Cd) is decreased when temperature increases from 600 to 700 • C. More research and experimental work is needed to completely analyze the heavy metal impact in biochar [56]. The microplastics are also removed at a temperature of 500 • C, which decreases the potential risk to the environment [57].…”
Section: Comparison Of Mass and Energy Balancesmentioning
confidence: 99%
“…However, the high heavy metal content greatly restricts utilization of sludge [23,24]. Thus, the quantity of heavy metals in sludge has always been a concern [25][26][27][28][29]. Azari et al [30] reported that compost concentrates or dilutes heavy metals in wastewater.…”
Section: Introductionmentioning
confidence: 99%